A portable pen-sized instrumentation to measure stiffness of soft tissues in vivo - Zhengwei Li (Nature Portfolio, 2021)
Abstract Quantitative assessment of soft tissue elasticity is crucial to a broad range of applications, such as biomechanical modeling, physiological monitoring, and tissue diseases diagnosing. However, the modulus measurement of soft tissues, particularly in vivo, has proved challenging since the instrument has to reach the site of soft tissue and be able to measure in a very short time. Here, we present a simple method to measure the elastic modulus of soft tissues on site by exploiting buckling of a long slender bar to quantify the applied force and a spherical indentation to extract the elastic modulus. The method is realized by developing a portable pen-sized instrument (EPen: Elastic modulus pen). The measurement accuracies are verified by independent modulus measures using commercial nanoindenter. Quantitative measurements of the elastic modulus of mouse pancreas, healthy and cancerous, surgically exposed but attached to the body further confirm the potential clinical utility of the EPen.